Veil, Nudity and Feminine in Iranian Scene - Yunis, Leandra (Malala, 2020)
This article presents a historical review about exposition of female body in Persian dance and its consequence to scenical art in XXth century Iran. It’s higlighted the central role of cinema and literature in the development of Iranian Nacional dance,  specially concering to inspiration in classical works and its Zoroastrian principle of genre equity that establishes an opposition to shi‘ism women familiar right. The importance of this study is due to the protagonization of women in performatic and dramaturgic Iranian arts starting in dance, the artistic language which concentrates the moral discution about body exhibition and obligatory use of veil.